Adsorption and Corrosion Inhibition Effect of Schiff Base Ligands on Low Carbon Steel Corrosion in Hydrochloric Acid Solution. Issue 6 (2nd June 2016) - Soltani, N.; Salavati, H.; Rasouli, N.; Paziresh, M.; Moghadasi, A.
Abstract : In this study, the corrosion inhibition of low carbon steel in 2.0 mol L −1 HCl by N, N′-bis(salicylidene) benzidine (Schiff base A) and N, N´-bis(5-nitrosalicylidene) benzidine (Schiff base B) has been studied using chemical (weight loss) and electrochemical (potentiodynamic polarization and electrochemical impedance spectroscopy, EIS) measurements. Polarization curves reveal that the used compounds are mixed-type inhibitors. Results show that the inhibition efficiency increases when the inhibitor concentration increases and the inhibition efficiency follows the order: Schiff base B > Schiff base A. The obtained experimental data fitted Langmuir adsorption isotherm. Also, associated activation parameters ( E a, Δ H *, and Δ S *) and the thermodynamic adsorption parameters ( K ads, Δ ) were calculated and discussed. Quantum chemical calculations were performed to theoretically define the relationship between molecular structure and inhibition efficiency of Schiff base A and Schiff base B.